Implementation of Total Productive Maintenance (TPM) Using Overall Equipment Effectiveness (OEE) Method on HPLC Instruments in Laboratory - Jannahti, Adik Bela; Lasmana, Cecep; Fauzi, Muchammad (JTI: Jurnal Teknik Industri, 2024)
The study aimed to assess the efficacy of HPLC instruments in a pharmaceutical laboratory at PT. XYZ by evaluating three OEE matrices (availability, performance, and quality) and identifying the losses leading to low OEE scores affecting the chromatography process performance. The method used is quantitative to calculate the availability rate, performance rate, and quality ratio based on the breakdown data and quantity of product data, followed by calculating the OEE score and comparing the obtained OEE and the world-class standard OEE score. The results demonstrate that the average availability rate in 2022 is 90,73%, the performance rate is 90,45%, and the quality ratio is 95,55%, resulting in the OEE score of 78,42%, which does not meet the world-class OEE standards score. To identify the problems causing the low OEE score, a qualitative analysis is performed using Current Condition Analysis and Fish Bone Diagram. Research indicates that five factors contribute to low OEE scores for HPLC instruments in PT. XYZ, including Method, Man, Machine, Material, and Environment. For each factor, the proposed improvement is described to increase the OEE score, including establishing the maintenance procedure, a training program for laboratory personnel, inventory management for spare parts, and an operating procedure. Keywords: Total Productive Maintenance, Overall Equipment Effectiveness, HPLC, Fish Bone Diagram